Pengaruh Virtual Private Network (VPN) Terhadap Keamanan dan Performa Akses Jaringan - Ali, Toni Saidun; Santoso, Imam; Quiko, Alfonso Sabatani (Jurnal Rekayasa Komputer, 2025)
Virtual Private Networks (VPN) represent a popular solution for securing network access, particularly within the context of remote work and sensitive data access. However, VPN usage also affects network performance metrics such as latency and access speed. This study aims to evaluate the impact of VPNs on network security and performance utilizing a Research and Development approach. Experimental results demonstrate a 65% increase in access security alongside a 22% decrease in performance, with variations depending on the type of VPN protocol deployed. With the growing demand for personal data protection, VPNs play a vital role in maintaining privacy and securing digital communications. Nevertheless, the impact of VPN usage on network performance, specifically regarding access speed and latency, frequently remains a subject of debate. The research findings show that although VPNs can reduce access speed, newer technologies such as WireGuard and IKEv2 have mitigated these negative performance impacts. This study provides useful insights for individuals and organizations in selecting VPN services that align with their specific requirements.